(untitled) (International relations and international law Journal, 2016)
Germany ad heres the idea of reforming Security Council. German politicians believe that UN’s most important body in XXI century must be appropriate to a new international environment. In order to achieve this UN must abandon approaches toward a world that more fit to 1945. In the era of global changes, new risks and challenges Security Council can become efficient and capable body only in case of reformation and abandonment of unilateral approach towards world politics. Germany has a long and specific path in UN including all contradictions of second half of the XX century. Germany six times held the position of Security Council’s non-permanent member and now this country together with Brazil, India and Japan within frame of «Big 4» (G4) calls for UN’s overall reformation. Federal Republic’s new foreign policy declares its responsibility for international security, stability and order in a new world and Germany’s participation in reforming UN. Permanent membership in UN Security Council will strengthen Germany’s positions.